A Study to Assess the Effectiveness of Neurobic Exercise on Cognitive Impairment Among Post Stroke Old Age People at Selected Community Area, Namakkal District - Sathiya.S; Uma.K; Radha.S; Jamunarani.M (The Bioscan, 2025)
Background: Cognitive impairment after stroke has a significant impact on the quality of life of elderly patients. Neurobic exercise, a cognitive stimulation method involving physical and mental activity, has been suggested as a valuable intervention. The current study assesses its effect on cognitive function in post-stroke elderly patients. Methods: A quasi-experimental design involved 60 elderly patients after stroke, assigned to an experimental group that underwent neurobic exercise and a control group receiving normal care. Cognitive function was measured before and after the intervention using standardized assessment tools. Statistical tests defined the significance of improvements. Results: Pretest results indicated that 66.67% of the experimental group had moderate cognitive impairment and 33.33% had mild impairment. Following neurobic exercise, 63.33% attained normal cognitive function and 36.67% had mild impairment. In the control group, however, only 10% attained normal cognition, with 70% still having moderate impairment and 20% having mild impairment. Between-group analysis validated significant cognitive improvement in the experimental group. Younger and married participants also showed improved recovery outcomes. Conclusion: Neurobic exercise is an extremely efficient non-pharmacological tool for cognitive rehabilitation in post-stroke patients. Considering its ease of access and efficacy, it should be incorporated into standard rehabilitation protocols. Long-term compliance, computerized cognitive training, and multicentric validation are areas to be investigated in future studies.